Analysis of the Degradation of Nutritional and Bioactive Components of Purple Sweet Potato during Drying into Flour Using Cabinet Dryer - Putra, Reski Praja; Sukainah, Andi; Mukhlis, Andi Muhammad Akram; Yulianti, Yulianti; Annisa, Khaerung (Journal of Agroscience Indonesia, 2023)
Sweet potato has the potential to be developed as a source of raw material for making flour to substitute the use of wheat flour. The sweet potatoes used in this study as flour were sweet potatoes with purple flesh. Processing of purple sweet potato into flour can be done through the drying process. The purpose of this study was to evaluate the effect of the temperature used in the cabinet dryer on the rate of degradation of the nutritional components and bioactive components of purple sweet potato during the flouring process. Purple sweet potato is cleaned and made into chips with a size of ± 2 mm and then dried in a cabinet dryer. The variables in this study were temperature (50 ºC, 55 ºC, 60 ºC) and drying time (1, 2, 3, 4, 5, 6, 7, 8 hours). Each treatment was repeated 3 times and observed for water content, total sugar, reducing sugar, beta-carotene, anthocyanins, polyphenols, and antioxidant activity. Data were analyzed using a Completely Randomized Factorial Design followed by Duncan's Test. The results showed that temperature and drying time had a significant effect on the nutritional and bioactive components of purple sweet potato during the drying process. A temperature of 60 ºC can be recommended as one of the temperatures used to dry purple sweet potatoes with a drying time of 5 hours. At this temperature and drying time, the anthocyanin content and antioxidant activity still have their biological properties. The characteristics of purple sweet potato slices in this treatment were 9.62% water content, 0.84% total sugar, 0.52% reducing sugar, 0.74% beta-carotene, 25.25% anthocyanins, 4.93% polyphenols, and 2.29% antioxidant activity.